Effect of Foaming Temperature on Microstructure, Mechanical Properties and Flame Spread Rate in PET–PEN Copolymer - Byung Kyu Park; Charn-Jung Kim; Byeong Jun Lee (Energies, 2021)
Polymer foams are expanding their applications into functional materials. Partial foam structure has been fabricated in polyethylene terephthalate–polyethylene naphthalate (PET–PEN) copolymer by solid state foaming. Through SEM image analyses, a potential to fabricate gradient foam structures with micropores and unfoamed skin layers has been identified. The post-foaming temperature Tf tune the pore size distribution. Radial distribution of micromechanical properties, indentation hardness and elastic modulus were measured for the partial foam and their values were around 0.12 GPa and 2.0 GPa, respectively, for the outer foamed region. Foaming temperature affects the glass transition temperature Tg, the coefficient of thermal expansion and the flame spreading rate. For the range of Tf ≤ 60°C, thermal expansion coefficients for T > Tg are about 0.5 m/m°C (steep expansion group, SEG). When Tf is above 80 °C, they are around 0.02 m/m°C (mild expansion group, MEG). The burning rate of SEG is 2.8 times higher than that of MEG.